2022
DOI: 10.3390/app121910111
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Influence of User and Graphic–Text Combined Icon Construal Level Fitting on Visual Cognition

Abstract: Based on the individual traits of the user’s construal level differences, this study examines the visual cognition differences of graphic–text combined icon concreteness in the interface between users with high and low construal levels. We classified four types of graphic–text combined icons, which are as follows: concrete graphic + concrete text (Ci + Ct), concrete graphic + abstract text (Ci + At), abstract graphic + concrete text (Ai + Ct), and abstract graphic + abstract text (Ai + At). According to the be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…The results showed that the best search performance was achieved with a vertically symmetrically arranged layout, which provided a reference for the GIS interface layout. Zhu et al (2022) explored the differences in users' visual perception characteristics of the two visual parameters, graphics and text, and pointed out that the design of combination icons should choose a concrete match between graphics and text to reduce the cognitive load.…”
Section: Visual Parameters As Predictors Of Interface Designmentioning
confidence: 99%
“…The results showed that the best search performance was achieved with a vertically symmetrically arranged layout, which provided a reference for the GIS interface layout. Zhu et al (2022) explored the differences in users' visual perception characteristics of the two visual parameters, graphics and text, and pointed out that the design of combination icons should choose a concrete match between graphics and text to reduce the cognitive load.…”
Section: Visual Parameters As Predictors Of Interface Designmentioning
confidence: 99%